2019
DOI: 10.25518/0037-9565.8429
|View full text |Cite
|
Sign up to set email alerts
|

Étude ethnobotanique et inventaire des plantes médicinales dans la région de Bougous

Abstract: De nos jours, malgré le développement de la chimie de synthèse, l’utilisation des plantes médicinales a conservé une large place du fait de leur efficacité dans diverses procédures thérapeutiques. Actuellement, leur utilisation occupe une place primordiale dans la vie de l’homme. En effet, les connaissances ancestrales sont transmises de générations en générations, permettant ainsi la conservation de ce savoir. L’objectif du travail mené a été de dresser d’une part un inventaire floristique de la région de Bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 5 publications
7
8
0
2
Order By: Relevance
“…In similar, results of recent research are shown that the uses of spontaneous medicinal plants are so superior (90 %) to cultivating species (10 %) 21 . this finding about growth forms with (59 % of spontaneous plants) and (41 % of cultivated species) has been reported by another author 22 . The concentrations of bioactive substances in medicinal plants (spontaneous or cultivated species) change depending on several factors.…”
Section: Discussionsupporting
confidence: 82%
“…In similar, results of recent research are shown that the uses of spontaneous medicinal plants are so superior (90 %) to cultivating species (10 %) 21 . this finding about growth forms with (59 % of spontaneous plants) and (41 % of cultivated species) has been reported by another author 22 . The concentrations of bioactive substances in medicinal plants (spontaneous or cultivated species) change depending on several factors.…”
Section: Discussionsupporting
confidence: 82%
“…In Algeria, these results agree with those obtained by Chermat and Gharzouli (2015); Boughrara and Legseir (2016), Bouasla and Bouasla (2017); Hamel et al (2018), Lazli et al (2019) and Bouhouia (2021). In Morocco, they agree with those of Salhi et al (2010); Lahsissene and Kahouadji (2010);Hseini et al, 2011;Tahri et al, 2012;Rhattas et al, 2016;Belhaj et al, 2020 and in Tunisia, with those of Jdaidi and Hasnaoui (2016).…”
Section: Diseases Treatedsupporting
confidence: 91%
“…Moreover, in Algeria, the results obtained relating to the modes of use of the plants listed are identical to those obtained by Aouadi (2021) and Lazli et al (2019) at the level of the El Kala region of the wilaya of El Tarf. They are also consistent with the results of work carried out in other regions at the national and international level (Benkhnigue et al, 2010(Benkhnigue et al, -2011Tahri et al, 2012;Bouzid et al, 2017;Bouasla and Bouasla, 2017;Hadjadj et al, 2019;Belhaj et al, 2020;Rahayu et al, 2021a).…”
Section: Mode Of Usessupporting
confidence: 85%
See 1 more Smart Citation
“…This allowed us to have a wide assortment of data on the conventional utilization of therapeutic plants. Our survey performed from 2013 to 2015 helped distinguish several species used by local people in traditional medicine [10][11][12].…”
Section: Statistical Study Of Areamentioning
confidence: 99%